Legal protection of KSPPS members in the use of the exoneration clause in Central Java - Moh. Arifin; Ali Maskur; Afif Noor (Ulul Albab: Jurnal Studi dan Penelitian Hukum Islam, 2020)
Legal protection for members of the Cooperative for Savings Loans and Sharia Financing (KSPPS) is important to protect the rights of cooperative members in accordance with Law Number 8 of 1999 concerning Consumer Protection. In loans practices, KSPPS often uses a standard agreement which includes an exoneration clause for time effectiveness and efficiency. However, the use of a standard agreement that contains an exoneration clause is more beneficial to the KSPPS and disadvantages the cooperative members as consumers because as a member of the consumer cooperative they do not have the opportunity to negotiate the contents of the standard agreement and must forcefully agree on the standard agreement so that the financing application he submits is granted by KSPPS.This research is an empirical juridical study with a conceptual and statutory approach using qualitative analysis. This research was conducted at KSPPS in Central Java by taking samples from five districts / cities based on residency areas. The results of this study indicate that the standard agreement containing the exoneration clause is still often used by KSPPS, therefore it is necessary to disseminate information to cooperative managers and cooperative members in order to minimize the use of standard agreements containing exoneration clauses so that the rights of the parties can be fulfilled and avoid elements of defects of will which is contrary to the principles in the agreement.